2021
DOI: 10.1111/1759-7714.14252
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab monotherapy versus pembrolizumab plus chemotherapy in patients with non‐small‐cell lung cancer: A multicenter retrospective trial

Abstract: Background: Pembrolizumab alone or in combination with chemotherapy is a standard treatment for patients with non-small-cell lung cancer (NSCLC) with high programmed death-ligand 1 (PD-L1) expression. However, no study has compared the efficacies of these two regimens. Therefore, we aimed to compare the efficacy of pembrolizumab alone and in combination with chemotherapy in NSCLC patients with high PD-L1 expression. Methods: We conducted a multicenter retrospective trial involving patients with diagnosed unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In clinical practice, targeted therapy, radiotherapy, and chemotherapy combined with immunotherapy have been applied successfully in various tumors. 431 433 Therefore, we summarized clinical trials of some novel autophagy, pyroptosis, ferroptosis, and necroptosis inducers/inhibitors, chemotherapy, radiotherapy, and targeted therapy combined with immunotherapy (Table 3 ).…”
Section: New Advances In Targeting Autophagy Pyroptosis Ferroptosis A...mentioning
confidence: 99%
“…In clinical practice, targeted therapy, radiotherapy, and chemotherapy combined with immunotherapy have been applied successfully in various tumors. 431 433 Therefore, we summarized clinical trials of some novel autophagy, pyroptosis, ferroptosis, and necroptosis inducers/inhibitors, chemotherapy, radiotherapy, and targeted therapy combined with immunotherapy (Table 3 ).…”
Section: New Advances In Targeting Autophagy Pyroptosis Ferroptosis A...mentioning
confidence: 99%
“…Although the study results favored combination therapy, subsequent real-world studies demonstrated similar PFS and OS among patients who received different treatment modalities [11,12,14]. On the contrary, a multicenter retrospective cohort study conducted by Matsumoto et al showed that pembrolizumab monotherapy provided longer PFS than combination therapy in the subgroup of patients with metastases to the liver, lung, adrenal glands, bone, or lymph nodes [13]. Moreover, a retrospective study using electronic databases of four Israeli cancer centers showed that pembrolizumab monotherapy and combination therapy with pembrolizumab and chemotherapy provided similar OS in patients with high PD-L1 expression after propensity score matching, and a significantly longer median OS was observed only in female patients who received the combination therapy [11].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, cohort studies comparing treatment efficacy of pembrolizumab alone or in combination with chemotherapy have been carried out, but no significant difference in survival outcomes was observed amongst patients who received different treatment modalities [11][12][13][14]. The possible reasons for the insignificant difference might be attributed to the higher toxicities in combination therapy [14] and its limited clinical benefits in certain patient subgroups [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pembrolizumab is the first-line therapy for patients with PD-L1 50% or greater as when pembrolizumab is used as monotherapy there were no significant differences in PFS, OS and respond rate (RR) compared to pembrolizumab combined with chemotherapy and pembrolizumab (2 mg/kg every 3 weeks or 10 mg/kg every 2 or 3 weeks) showed 3-year OS rate in 35% of patients who received pembrolizumab compared to13% of patients who received docetaxel (chemotherapy) [27,28]. Pembrolizumab showed 5-year OS for patients who have PD-L1 50% or greater either these patients are previously treated patients or treatmentnaive patients and only grade 3 adverse events occurred, and grade 4 adverse events aren't documented [29].…”
Section: Pembrolizumabmentioning
confidence: 98%